DERAJAT APOPTOSIS SEL GANGLION RETINA PASCA PEMBERIAN TAMBAHAN EKSTRAK MORINGA OLEIFERA ORAL DIBANDINGKAN DENGAN TERAPI STANDAR Studi Eksperimental pada Tikus Wistar Model Methanol Toxic Optic Neuropathy: Oral Presentation - Experimental Study - Resident - ADELIA BAYU ISFANDIARI,; RISKI PRIHATNUNGTIAS,; FIFIN LUTHFIA RAHMI, (Ophthalmologica Indonesiana, 2024)
AbstractIntroduction & Objectives : Methanol toxic optic neuropathy can lead to retinal ganglion cell apoptosis which causes visual disturbance. Moringa oleifera has been reported to have an anti-inflamatorry effect that can prevent inflammatory mediators from being relased in methanol toxic optic neuropathyMethods : Twenty-one Wistar methanol toxic optic neuropathy were divided into 3 groups, namely base line group, control group that given intravenous methylprednisolone 4.5mg/6 hours for 3 days, and given standard theraphy and additional administration of oral Moringa oleifera 300mg/kgbodyweight/day for 4 weeks. Assessment of the degree of apoptosis by Anatomical Pathology with histopatolocigal scaoring. The study used Mann Whitney comparative hypothesis test (Significant p